(Supplement 1) Weather pattern definitions for India (1979 to 2016), link to netCDF files - Robert Neal; Joanne Robbins; Rutger Dankers; Ashis Mitra; Amal Jayakumar; E N Rajagopal; George Adamson (PANGAEA, 2019)
Mean u- and v- component wind fields at 850-hPa are provided over India for a set of 30 objectively derived weather patterns, which were generated by k-means clustering of daily (1200 UTC) reanalysis fields from ERA-interim between 1979 and 2016. The weather patterns are defined on a 1 x 1 degree resolution grid, which covers the area from 62 degrees west to 98 degrees west and 2 degrees north to 37 degrees north. The boundary coordinates represent the central positions of the outer grid points.
In supplement to: Neal, R et al. (2020): Deriving optimal weather pattern definitions for the representation of precipitation variability over India. International Journal of Climatology, 40(1), 342-360, https://doi.org/10.1002/joc.6215